Genes, training, and other constraints on individual performance: A role for dynamical systems theory? - Davids, K. (Sportscience, 2001)
Behavioral genetics and psychology provide useful insights into relative contributions of nature and nurture to variation in physical performance in a population, but understanding and exploiting these and other constraints on performance in individual athletes requires an over-arching multi-disciplinary theoretical framework. Dynamical systems theory, which has enjoyed some recent success in accounting for behavior of complex systems, may be the appropriate framework.